Into the forest : the secret language of trees - Hitchcock, Susan Tyler (National Geographic, 2022)
"For millennia, trees have offered renewal and inspiration. They have provided for humanity on every level, from spiritual sanctuary to the raw material for our homes, books, and food. In this beautiful and revealing book, National Geographic combines legendary photography with cutting-edge science to illuminate exactly how trees influence the life of planet Earth--from our personal lives to the weather cycle. Beautifully illustrated essays tell the stories of the world's most remarkable trees, from Tane Mahura in New Zealand, the ancient Maori "lord of the forest," to Pando, a single aspen spreading over 100 acres: Earth's largest living thing. You'll also discover how an astronaut carried tree seeds to the moon and back; the reason "microdosing" on tree gas is a sure way to boost your immune system; and why playing in the dirt boosts serotonin, happiness hormone"--Amazon.